Glutaredoxin AtGRXC2 catalyses inhibitory glutathionylation of Arabidopsis BRI1-associated receptor-like kinase 1 (BAK1) in vitro - Bender, Kyle W.; Wang, Xuejun; Cheng, George B.; Kim, Hyoung Seok; Zielinski, Raymond E.; Huber, Steven C. (PORTLAND PRESS LTD, 2015)
Reversible protein phosphorylation, catalysed by protein kinases, is the most widely studied post-translational modification (PTM), whereas the analysis of other modifications such as S-thiolation is in its relative infancy. In a yeast-two-hybrid (Y2H) screen, we identified a number of novel putative brassinosteroid insensitive 1 (BR1)-associated receptor-like kinase 1 (BAK1) interacting proteins including several proteins related to redox regulation. Glutaredoxin (GRX) C2 (AtGRXC2) was among candidate proteins identified in the Y2H screen and its interaction with recombinant Flag-BAK1 cytoplasmic domain was confirmed using an in vitro pull-down approach. We show that BAK1 peptide kinase activity is sensitive to the oxidizing agents H2O2 and diamide in vitro, suggesting that cysteine oxidation might contribute to control of BAK1 activity. Furthermore, BAK1 was glutathionylated and this reaction could occur via a thiolate-dependent reaction with GSSG or a H2O2-dependent reaction with GSH and inhibited kinase activity. Surprisingly, both reactions were catalysed by AtGRXC2 at lower concentrations of GSSG or GSH than reacted non-enzymatically. Using MALDI-TOF MS, we identified Cys(353), Cys(374) and Cys(408) as potential sites of glutathionylation on the BAK1 cytoplasmic domain and directed mutagenesis suggests that Cys(353) and Cys(408) are major sites of GRXC2-mediated glutathionylation. Collectively, these results highlight the potential for redox control of BAK1 and demonstrate the ability of AtGRXC2 to catalyse protein glutathionylation, a function not previously described for any plant GRX. The present work presents a foundation for future studies of glutathionylation of plant receptor-like protein kinases (RLKs) as well as for the analysis of activities of plant GRXs.
Keywords: CASTOR-OIL SEEDS; PROTEIN-KINASE; PHOSPHOENOLPYRUVATE CARBOXYLASE; REDOX REGULATION; PHOTOSYNTHETIC ORGANISMS; TYROSINE PHOSPHORYLATION; S-GLUTATHIONYLATION; STRUCTURAL BASIS; ACTIVATION; BRI1